Brève incursion dans l’art de la représentation médiévale du martyre / A Brief Introduction into the Art of Medieval Representation of Martyrdom - Adrian Stoleriu; Andreea-Irina Stoleriu (Anastasis: Research in Medieval Culture and Art)
From the first Christian centuries, martyrdom represented the most acute expression of suffering for the defence of faith in Jesus Christ. The violent death suffered by those who kept a firm faith in the sacred values they confessed marked the whole Christian world from East to West, and offered an example of infinite courage and above all an undeniable model of holiness. This paper is a research on different forms of martyrdom and the artistic expressions used in their visual representation in the Middle Ages, briefly recalling some of the most remarkable creations of Christian art.